Modelling the Turbocharger Cut Off Application Due to Slow Steaming Operation 12RTA96C-B Engine - Karsten Wehner; Hartmut Schmidt; Muhammad Ramadhan Pamungkas (International Journal of Marine Engineering Innovation and Research, 2017)
Out of the total operational costs of a ship, fuel costs account for by far the highest proportion. In view of the global economic situation and the rising oil prices, shipowners and charterers are looking for solutions to cut costs by reducing fuel consumption. Low load operation, also well-known as “slow steaming”, represents the currently most effective and popular measure to cut fuel costs and, in consequence, the total operational costs for increased competitiveness in the market. Low load operation is possible and there is an increasing trend to operate in these very low engine load ranges. As the engines were not designed for this operational condition, various retrofit modifications to the engine can compensate for this. By using low load operation, the reduction of the RPM gives problems when sailing at low speed. A turbocharger (TC) compresses inlet air to a high pressure and after cooling this compressed air it results in higher mass of air in the cylinder. But when running at a low power load this air reaches temperatures that are too low for an optimal combustion process. One of the solution comes from the company Wärtsilä. They install so called “low steam engine kits”. When this kit is installed it allows the engine operators to cut off one turbocharger of the engine, this result’s in a higher RPM for the operating turbochargers. When the remaining TC’s have a higher RPM their efficiency improves and gives the engine more air for combustion.The goal of this Bachelor thesis is to make a calculation modelling and prove that by switching off one or more turbocharger on the system will improve the efficiency in slow steaming operation. Beside that, this thesis is aims to estimated the performance of the engine in both operation condition.